2021
DOI: 10.3390/ijerph18115665
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Determinants of Smoking in the Kingdom of Saudi Arabia

Abstract: Tobacco consumption, or smoking, is a major cause of preventable morbidity and mortality worldwide, including in the Kingdom of Saudi Arabia (KSA). In order to reduce the consumption of tobacco products, it is necessary to understand the factors that drive it. However, little is known about the socioeconomic determinants of tobacco smoking in the KSA. This study, therefore, investigates the socioeconomic factors that influence tobacco smoking in the KSA. Using a national health survey, the study employs logist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 23 publications
(52 reference statements)
4
20
1
Order By: Relevance
“…29 Our result is consistent with studies published in 2020 and 2021 indicating that no association was observed between education and intention to quit smoking. 7,29,34 Our estimates of price elasticity of demand corresponded with the changes in taxation policy that increased prices. The positive elasticity figures for the years from 2013 to 2015 were not in alignment with the goals of WHO and the World Bank to reduce consumption by increasing prices.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…29 Our result is consistent with studies published in 2020 and 2021 indicating that no association was observed between education and intention to quit smoking. 7,29,34 Our estimates of price elasticity of demand corresponded with the changes in taxation policy that increased prices. The positive elasticity figures for the years from 2013 to 2015 were not in alignment with the goals of WHO and the World Bank to reduce consumption by increasing prices.…”
Section: Discussionmentioning
confidence: 73%
“…8 Gross domestic product lost due to smoking increased from 0.2% in 2012 to 0.98% in 2016. 7 From 2010 to 2014, the cost of import of cigarettes and other tobacco products to Saudi Arabia was worth $3.4 billion. 9 Saudi ranks in the fourth position in tobacco sales and imports across the world.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations